Shadow riders - L'Amour, Louis (Toronto New York Bantam Books, 1982)
At the close of the Civil War, two brothers who fought on opposite sides return home to Texas to discover that their sisters have been kidnapped by Rebel guerrillas who refuse to accept the defeat of the Confederacy
89697